Naevoid psoriasis and ILVEN: Same coin, two faces? - Sujata Sengupta; Jayanta Kumar Das; Asok Gangopadhyay (Wolters Kluwer Medknow Publications, 2012)
The true existence of naevoid psoriasis and inflammatory linear verrucous naevus as distinct entities has been a debatable issue. Each has been opined to be a variant of the other. Considerable clinical and histological resemblance is seen between the two conditions. We describe three cases which attempt to throw more light on this issue.